The Sandwich Generation Phenomenon from the Perspective of Hadith: The Principle of al-Tawazun in Parent-Child Relations - Damayanti, Amelia; Muthoharoh, Isnaini Lu'lu' Atim (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
The sandwich generation often faces an ethical dilemma between fulfilling filial responsibilities toward parents and meeting the needs of their own families. This study examines the sandwich generation phenomenon from the perspective of hadith by focusing on the roles of parents and children and the principle of al-tawazun, or balance, in regulating family responsibilities. Using library research and a hadith-based qualitative approach, the study draws on authoritative hadith collections, hadith commentaries, and contemporary literature on family responsibility and multigenerational care. The data were identified, classified, and analyzed through thematic content analysis to formulate normative patterns concerning maintenance, filial responsibility, financial capacity, and psychological burden. The study argues that the obligation of parents to provide maintenance for children has clear normative limits, particularly in relation to basic needs and protection, and must be adjusted to parents’ financial capacity. Adult children who are able to work are not generally considered financially dependent on their parents, except under specific conditions of incapacity, such as illness or physical limitation. Conversely, children’s responsibility toward parents must also be understood proportionately and should not be imposed beyond their objective capacity. The study proposes three analytical indicators for reading the sandwich generation phenomenon through al-tawazun: the priority of rights, the limits of financial capacity, and the limits of psychological burden.